West European Opinion on Security Issues. - United States. International Communication Agency. Office of Research.; McLellan, Robert S. (Tufts University. Tisch Library., 2019)
In April-May 1981, the International Communication Agency (USICA) sponsored surveys of elite opinion in Britain, France, Italy and West Germany with about 300 influentials in government, politics, business, banking and the media. The results, when combined with the findings from USICA general public opinion polls in these countries as well as Norway and the Netherlands conducted between April and July 1981 provide a reading of West European views on security issues prior to President Reagan's November 18 address on nuclear weapons in Europe.; Research Report R-19-81